On the Transience of Things and Memory of the Past: An Old Polish Dialogue with the Antique Tradition (Benedykt Chmielowski’s “New Athens”) - Wichowa, Maria (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2015)
The paper investigates the reflection on the passing of time, time’s nature and on the memory of the Antiquity presented in New Athens by Rev. Benedykt Chmielowski, as part of an ancient tradition cultivated in this first Polish encyclopaedia. The writer emphasized continuity and high importance of tradition and observed the process of creative development of the values bequeathed by the past. He believed modern people to be followers and inventors, perfecting the cultural goods produced by the antiquity. In Volume III of his work Chmielowski published a discourse on the following topic: ‘Which age, the old or the new one, is more polished?’ and demonstrated the superiority of the antiquity. He believed that his contemporaries drew abundantly on the ancient tradition and appreciated the greatness of the achievements of ancient intellectuals and artists, but did not surpass them in any way, simply processing what they received as inheritance. The encyclopaedist was convinced that the culture of his epoch relied completely on the ancient tradition.